Analisis Website Quality, Customer Satisfaction dan Repurchase Intention pada Bisnis E-Commerce di Indonesia - Mavilinda, Hera Febria; Nazaruddin, Akhmad (Jurnal Bisnis dan Manajemen, 2022)
The purpose of this study are to analyze the effect of website quality on repurchase intention through customer satisfaction as a mediating variable. The type of this research is quantitative research with experimental research methods. The sample in this study are 200 respondents. The sampling technique used is non-probability sampling technique. Hypothesis testing using the Structure Equations Modeling. Based on the results, it shows that website quality has a significant direct effect on customer satisfaction and an indirect effect on repurchase interest through customer satisfaction as a mediating variable. The results also show that the website quality variable has no direct effect on repurchase intention.